UNIFORM LACUNARY STATISTICAL CONVERGENCE ON TIME SCALES - Yilmaz, E.; Mohiuddine, S. A.; Altin, Y.; Koyunbakan, H. (Etamaths Publ, 2017)
We introduce (theta, m)-uniform lacunary density of any set and (theta, m)-uniform lacunary statistical convergence on an arbitrary time scale. Moreover, (theta, m)-uniform strongly p-lacunary summability and some inclusion relations about these new concepts are also presented.
Keywords: uniform lacunary statistical convergence; sequence spaces; time scale